Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan dan Corporate Social Responsibility Pada Kebijakan Dividen - Arjana, I Putu Pande Hary; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi, 2017)
One of the attractions of investing for investors in both primary and secondary markets is dividends. In order for a company to be able to pay dividends to shareholders, the company must be able to generate profits. Profit is one benchmark to judge whether a company has a good or bad performance. The allocation of the determination of profit as retained earnings and dividend payout is a key aspect of dividend policy. Dividend policy is the company's decision regarding the determination of whether the profits earned by the company will be distributed in dividends to shareholders or to be retained in the form of retained earnings based on decisions obtained through the Meeting General Shareholders. Dividends shared by the company reflect the company's ability to earn profits and ensure good prospects in the future. This study aims to determine the effect of profitability, leverage, firm size, and corporate social responsibility on dividend policy. This research was conducted at a manufacturing company listed on Indonesia Stock Exchange (BEI) in the period 2013-2015. The number of samples used as many as 51 companies listed on the Stock Exchange. The method of determining the sample using purposive sampling method by using multiple linear regression analysis technique. Based on the results of the analysis shows that: Profitability affects dividend policy, Leverage does not affect dividend policy, firm size affects dividend policy, and Corporate social responsibility influences dividend policy.